PERTANGGUNGJAWABAN PIDANA TERHADAP PELAKU TINDAK PIDANA PENIMBUNAN OBAT TERAPI COVID-19 - muhammad chaidir satria; yuli kasmarani (Universitas Islam Negeri Raden Fatah Palembang, 2022)
ABSTRACT The title of this research is criminal responsibility for the perpetrators of the criminal act of hoarding Covid-19 therapeutic drugs based on law number 36 of 2009 concerning health. Hoarding of drugs is something that is prohibited both in Indonesian legislation and in Islamic law, especially during the Covid-19 pandemic, of course, it can cause misery and loss in society. The problem raised in this study is criminal liability for the criminal act of hoarding Covid-19 therapeutic drugs. The method used in this research is a normative research method or what is often called library research. The results of this study can be seen that criminal liability for the perpetrators of the criminal act of hoarding Covid-19 therapeutic drugs can be sentenced to a maximum of 10 (ten) years in prison and a maximum fine of Rp. 1,000,000,000.00 in addition, can be punished with a sentence of 5 (five) years and/or a maximum fine of Rp. 50,000,000,000.00 (fifty billion rupiah). Furthermore, in Islamic criminal law, criminal responsibility for the criminal act of hoarding Covid-19 therapeutic drugs is subject to ta'zir punishment, the punishment of which is left to the government or local authorities. Keywords: Criminal Liability, Hoarding, Ikhtikar, Covid-19.